2019
DOI: 10.1093/ehjcr/ytz141
|View full text |Cite
|
Sign up to set email alerts
|

Micro-reentry right atrial tachycardia originating from fossa ovalis: a case report of high-density mapping by PentaRay catheter

Abstract: Background Micro-reentry tachycardia usually emerges in scar tissues related to post-atrial fibrillation ablation and cardiomyopathy. It is difficult to identify the micro-reentry circuit accurately by conventional mapping method. Case summary A 74-year-old man presented with paroxysmal atrial tachycardia (AT) presenting as palpitations. He was evaluated by an electrophysiological examination using a high-density CARTO mappin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…High‐density mapping with multielectrode catheters may decrease procedure time and increase ablation success 56 . Although none of the patients in our review had microreentry, high‐density mapping has recently been reported to be useful in defining circuits and best ablation sites 57,58 …”
Section: Discussionmentioning
confidence: 90%
“…High‐density mapping with multielectrode catheters may decrease procedure time and increase ablation success 56 . Although none of the patients in our review had microreentry, high‐density mapping has recently been reported to be useful in defining circuits and best ablation sites 57,58 …”
Section: Discussionmentioning
confidence: 90%
“…[7]. Although there are two reported cases of FAT arising from FOv [8,9], the left septal origin of FAT focusing on FOv has no written literature. The present case firstly reported a FAT arising from the left atrial mirroring position of FOv.…”
Section: Discussionmentioning
confidence: 99%
“… 6 Some studies demonstrate that the actual interatrial structure of the IAS is the FOV with its rim. 7 Although there are 2 reported cases of FAT arising from the FOv, 8 , 9 the left septal origin of FAT focusing on the FOv has no written literature. The present case firstly reported a FAT arising from the LA mirroring position of the FOv.…”
Section: Discussionmentioning
confidence: 99%